APPLICATIONS OF THE DERIVATIVE - Adham Normatov (Galaxy International Interdisciplinary Research Journal, 2022)
This article talks about determining the conditions for the function to remain constant in some interval, whether it is increasing or decreasing, whether it is convex or concave, turning points using the derivative, necessary and sufficient conditions. lib, assertions in each section are explained and reinforced with examples